Spinal cord gray matter demyelination in multiple sclerosis-a novel pattern of residual plaque morphology. - Gilmore, C; Bö, L; Owens, T; Lowe, J; Esiri, M; Evangelou, N (2006)
The extent and pattern of gray matter (GM) demyelination in the spinal cord in multiple sclerosis (MS) has not been examined in detail. Human autopsy material was obtained from 36 MS cases and 12 controls. Transverse sections were taken from five levels of the spinal cord (upper cervical, lower cervical, upper thoracic, lower thoracic and lumbar levels) and the extent of GM and white matter (WM) demyelination evaluated using proteolipid protein immunohistochemistry (IHC). The proportion of the GM that was demyelinated (33%) was significantly greater than the proportion of demyelinated WM (20%) (P < 0.0001). Similarly, demyelination was more extensive in the GM than in the WM at each of the five cord levels. The extent of GM demyelination was not significantly different between the five cord levels while WM demyelination was greatest at the upper cervical level. Morphologically, the borders of a proportion of the GM plaques show a strict respect for the GM/WM boundary. We demonstrate that extensive demyelination occurs in the GM of the spinal cord in MS. Myelin protein IHC reveals a novel pattern of residual plaque morphology challenging previous work suggesting that MS plaques display a total disregard for anatomical boundaries.